Online yoga to reduce post traumatic stress in women who have experienced stillbirth: a randomized control feasibility trial - Jennifer Huberty; Mariah Sullivan; Jeni Green; Jonathan Kurka; Jenn Leiferman; Katherine Gold; Joanne Cacciatore (BMC, 2020)
Abstract Background About 1 in every 150 pregnancies end in stillbirth. Consequences include symptoms of post traumatic stress disorder (PTSD), depression, and anxiety. Yoga has been used to treat PTSD in other populations and may improve health outcomes for stillbirth mothers. The purpose of this study was to determine: (a) feasibility of a 12-week home-based, online yoga intervention with varying doses; (b) acceptability of a "stretch and tone" control group; and (c) preliminary efficacy of the intervention on reducing symptoms of PTSD, anxiety, depression, perinatal grief, self-compassion, emotional regulation, mindfulness, sleep quality, and subjective health. Methods Participants (N = 90) were recruited nationally and randomized into one of three groups for yoga or exercise (low dose (LD), 60 min per week; moderate dose (MD), 150 min per week; and stretch-and-tone control group (STC)). Baseline and post-intervention surveys measured main outcomes (listed above). Frequency analyses were used to determine feasibility. Repeated measures ANCOVA were used to determine preliminary efficacy. Multiple regression analyses were used to determine a dose-response relationship between minutes of yoga and each outcome variable. Results Over half of participants completed the intervention (n = 48/90). Benchmarks (≥70% reported > 75% satisfaction) were met in each group for satisfaction and enjoyment. Participants meeting benchmarks (completing > 90% of prescribed minutes 9/12 weeks) for LD and MD groups were 44% (n = 8/18) and 6% (n = 1/16), respectively. LD and MD groups averaged 44.0 and 77.3 min per week of yoga, respectively. The MD group reported that 150 prescribed minutes per week of yoga was too much. There were significant decreases in PTSD and depression, and improvements in self-rated health at post-intervention for both intervention groups. There was a significant difference in depression scores (p = .036) and grief intensity (p = .009) between the MD and STC groups. PTSD showed non-significant decreases of 43% and 56% at post-intervention in LD and MD groups, respectively (22% decrease in control). Conclusions This was the first study to determine the feasibility and preliminary efficacy of an online yoga intervention for women after stillbirth. Future research warrants a randomized controlled trial. Trial registration ClinicalTrials.gov. NCT02925481 . Registered 10-04-16.